Training of 3D printing technology utilization for making learning props - Widiatmoko, Julian Anindito; Sufyan, Fendy Kussuma Hadi (Community Empowerment, 2025)
Teaching props can help make the learning process more effective by bringing students closer to a concept through a more tangible representation. However, many schools struggle to meet the need for teaching aids, as seen at SMA Sholihin in Bandongan District, Magelang Regency. With advancements in manufacturing technology, an affordable solution is now available to address this issue: 3D printing. The purpose of this community service program is to provide education on the utilization of 3D printing for developing teaching props. The method used involves training on the basic concepts of 3D printing, how to obtain 3D models, and how to operate a 3D printer. The material was delivered through presentations, discussions, and direct demonstrations of the process of creating three-dimensional objects using a 3D printer. At the end of the program, six educational teaching props were successfully produced using 3D printing, along with an improved understanding of the fundamentals of 3D printing technology, 3D modeling, and 3D printer operation.